Prevention of Osteoporosis. Four-Year Follow-Up of a Cohort of Postmenopausal Women Treated with an Ossein-Hydroxyapatite Compound - Fernandez-Pareja, Antonio; Hernandez-Blanco Еlena; Perez-Maceda, Jose Manuel; Rubio, Vicente Jose Riera; Palazuelos, Javier Haya; Dulmau, Jose Manasanch (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2009)
Background: The long-term effects of ossein-hydroxyapatite compound (OHC), a drug used for osteoporosis prevention, have not been previously reported. The aim of this study was to assess the long-term efficacy of OHC in postmenopausal women with bone mineral density (BMD) in the osteopenia range. Methods: We performed a retrospective 4-year follow-up study in a primary-care setting to assess changes in BMD in a cohort of 112 postmenopausal women included in an osteoporosis programme that included health and dietary advice and who were treated with OHC 1660mg every 12 hours. BMD was measured annually in the distal part of the forearm, with T- and Z-score values being calculated for trabecular and total bone. Results: A progressive and statistically significant increase in BMD was observed in trabecular and total T- and Z-score mean values. At baseline, mean ±SD trabecular T- and Z-scores were –1.27±0.7 and –1.03±0.7, respectively, and –0.86±0.7 and –0.62±0.7, respectively, at the end of the 4-year follow-up period (both p < 0.0001). Mild constipation was observed in 3.2% of patients during the follow-up period. Conclusion: Ossein-hydroxyapatite compound could be an effective and safe agent for the prevention of bone loss in postmenopausal osteopenic women, with significant increases in BMD being observed in this group of patients.